The role of citizen science in monitoring small-scale pollution events. Issue 1 (15th July 2017) - Hyder, Kieran; Wright, Serena; Kirby, Mark; Brant, Jan
Abstract: Small-scale pollution events involve the release of potentially harmful substances into the marine environment. These events can affect all levels of the ecosystem, with damage to both fauna and flora. Numerous reporting structures are currently available to document spills, however there is a lack of information on small-scale events due to their magnitude and patchy distribution. To this end, volunteers may provide a useful tool in filling this data gap, especially for coastal environments with a high usage by members of the public. The potential for citizen scientists to record small-scale pollution events is explored using the UK as an example, with a focus on highlighting methods and issues associated with using this data source. An integrated monitoring system is proposed which combines citizen science and traditional reporting approaches. Highlights: Small-scale pollution is under reported, so magnitude and impact is largely unknown. Mapping small-scale pollution using traditional methods is very challenging. Citizen science can document small-scale pollution if robust methods are used. A monitoring system that integrates citizen and traditional science is proposed.